Reproducibility of freehand vs. foam cast as well as the intrarater reliability of foam cast ultrasound scans assessing the muscle architecture and tissue organization of the gastrocnemius medialis and vastus lateralis muscles - Lesinski, Melanie; Bashford, Gregory; Markov, Adrian; Risch, Lucie; Cassel, Michael (Frontiers in Sports and Active Living, 2024)
Background: This study compares the reproducibility of freehand (FH) versus foam cast (FC) scans and investigates intra-rater reliability of ultrasound FC muscle architecture and tissue organization measurements of gastrocnemius medialis (GM) and vastus lateralis (VL) muscle with fixed and repositioning FC scans.: Thirteen young adults (22±3 years) underwent repeated sagittal B-mode ultrasound measurements of the GM and VL. FH, FC, and repositioned FC scans were conducted. Muscle architecture measurements included muscle thickness (MT), pennation angles (PA), and fascicle length (FL). Spatial frequency analysis (SFA) assessed muscle tissue organization.Results: MT decreased from 2.1 to 1.8 cm in GM and from 2.4 to 2.2 cm in VL with FC compared to FH.Reproducibility between FH and FC showed poor-good intraclass correlation coefficients (ICC) for MT (0.46-0.77) and PA (0.09-0.86) as well as poor-moderate ICCs for FL (0.41), with very low-moderate test-retest variability (TRV) (4-18%). Tissue organization indicated low-good ICCs (0.21-0.80) with lowmoderate TRV (4-19.5%).Re-scanning for fixed FC indicated excellent ICCs for MT (0.95-0.996), good for PA (0.77-0.90), and moderate for FL (0.73-0.76), with low TRV (5-10%) for both muscles. Tissue organization displayed moderate-good ICCs (0.61-0.87) with very low-low TRV (4-9%).For repositioned FC scans in GM and VL, MT showed good-excellent ICCs (0.86-0.98) with very low-low TRV (2-8%). PA and FL demonstrated moderate-good ICCs (0.57-0.75), with very low-moderate TRV (2-13%). Tissue organization revealed ICCs ranging from poor-good (0.13-0.87) for both muscles, with low-moderate TRV (5-18%).FC systematically reduced MT by 2-3 mm. Further, reproducibility revealed low ICCs and high data variability for several muscle architecture and tissue organization parameters. Thus, switching methods within a single study is not recommended. Nevertheless, FC ultrasound scans demonstrated excellent intra-rater reliability for assessing MT. Particularly in the case of fixed FC scans, moderate-excellent ICCs were observed for all muscle architecture and tissue organization parameters, accompanied by very low-low variability. Therefore, FC scans are recommended for investigating acute effects on muscle architecture and tissue organization, when FC can remain on the leg throughout measurements.